Capacitated lot-sizing with sequence dependent setup costs - Knut Haase (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
A new model is presented for capacitated lot-sizing with sequence dependent setup costs. The model is solved heuristically with a backward oriented method; the sequence and lot-size decisions are based on a priority rule which consists of a convex combination of setup and holding costs. A computational study is performed where the heuristic is compared with the Fleischmann approach for the discrete lot-sizing and scheduling problem with sequence dependent setup costs.
Keywords: 650; Lot-sizing; scheduling; sequence dependent setup costs; production planning and control; Produktionssteuerung; Theorie